The Nexus of Digital Learning Ecosystem, Techno-Pedagogical Self-Efficacy, and Teaching Competence of Selected Public Junior High School English Teachers in Misamis Oriental: A Sequential Explanatory Mixed Methods Study - Rodgen D. Palmes; Lydia Josefina R. Curaza (RIRAI Publisher, 2026)
This study investigated the relationship among the Digital Learning Ecosystem (DLE), Techno-Pedagogical Self-Efficacy (TPSE), and Teaching Competence (TC) among public junior high school English teachers in selected cities and municipalities of Misamis Oriental. Employing an explanatory sequential mixed-method design, quantitative data were first collected to determine the extent of DLE, the level of TPSE, and the degree of TC, as well as the relationships among these variables. Qualitative data from focus group discussions and in-depth interviews were subsequently gathered to explain and contextualize the quantitative findings. Results revealed that teachers generally experienced a high extent of digital learning ecosystem support, demonstrated high techno-pedagogical self-efficacy, and exhibited outstanding teaching competence. While a significant positive relationship was found between DLE and TPSE, neither DLE nor TPSE significantly predicted teaching competence. Mediation analysis further showed that TPSE did not significantly mediate the relationship between DLE and TC, and the null model emerged as the best-fitting structural model for teaching competence. Qualitative findings indicated that teaching competence is more strongly influenced by teacher agency, pedagogical translation, learner readiness, reflective practice, adaptability, and contextual realities than by digital resources and technological confidence alone. Based on the integrated findings, the study proposed the Contextually Mediated, Agency-Driven Digital ELT Upskilling Framework for Generative Teaching Competence, which conceptualizes teaching competence as a context-sensitive and process-driven outcome shaped by the interaction of digital support, pedagogy, teacher agency, and classroom conditions.